Transdermal delivery of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs): a mini review - Raditya Weka Nugraheni (Universitas Muhammadiyah Malang, 2019)
The transdermal route has several advantages over the oral route, especially for the drugs which significantly experience the first-pass effect in the liver. Another advantage of drug administration via the transdermal route is its non-invasive way and can be used by patients themselves. Also, it allows long-term use, thereby increasing patient compliance and is generally inexpensive. The development of transdermal preparation itself is not easy because of the permeability factor of drug ingredients through the skin is relatively low compared to the gastrointestinal route or mucous membrane because the skin is part of the body's defense system and prevents foreign materials to entering the body. The biggest challenge for drug administration via the transdermal route is that the limitations of drugs can be administrated through this route. NSAIDs are drugs that are widely used in chronic conditions and can cause serious gastrointestinal side effects. Therefore the transdermal route is expected to be a promising alternative in the future. The drug-loaded nanoparticle delivered using the iontophoresis method can improve the bioavailability of NSAIDs via the transdermal route.